370 The impacts of neoadjuvant chemotherapy and of cytoreductive surgery on ten-year survival from advanced ovarian cancer. (13th November 2020) - Kim, S; Kotsopoulos, J; Sun, P; Bernardini, M; Laframboise, S; Ferguson, S; Rosen, B; Narod, S; May, T
Abstract : Objective: To compare long-term survival outcomes for women with advanced ovarian cancer treated with chemotherapy, either before (neoadjuvant) or after surgery (primary cytoreductive) treated at a single tertiary cancer center. Methods: Retrospective hospital-based cohort study of 326 patients with stage IIIC or IV high-grade serous ovarian cancer who received neoadjuvant chemotherapy or primary cytoreductive surgery between 2001 and 2011. Clinical treatments were recorded and ten-year survival rates were measured. Results: A total of 183 women (56%) underwent primary cytoreductive surgery and 143 women (44%) received neoadjuvant chemotherapy. Women who had neoadjuvant chemotherapy were more likely to have no residual disease than those who underwent primary cytoreductive surgery (51.4% versus 41.5%) and they experienced inferior ten-year overall survival (9.1% versus 19.3%; p<0.0001). Among those who had primary cytoreductive surgery, those with no residual disease had superior ten-year overall survival than those who had any residual disease (36.0% versus 7.2%). Conclusion: Among women with advanced ovarian cancer, those who have undergone primary cytoreductive surgery have better survival than those who received neoadjuvant chemotherapy. Neoadjuvant chemotherapy should be reserved for patients who are not candidates for primary cytoreductive surgery.